Allah Sebagai Bapa dan Ibu: Studi Komparatif Dari Konstruksi Allah sebagai Bapa dalam Injil Matius dan Allah sebagai Ibu dalam Teologi Feminis - Pelita Hati Surbakti (Cipanas Theological Seminary, 2020)
Because it is considered as a product of androcentric culture that can bring up misogynists, some feminist Christian theologians reject the hegemony of the use of the word